MEDIA PEMBELAJARAN INTERAKTIF KHAN ACADEMY KIDS UNTUK MENINGKATKAN SOCIAL SKILL SISWA DI SEKOLAH DASAR - Yunus, Mahmud; Apit Dulyapit; Mira Amelia Amri; Linda Ika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Current learning requires interactive media for students to improve social skills. The purpose of this study was to determine whether there was an increase in students' social skills in the experimental class that participated in learning using the Khan Academy Kids application compared to the control class. This study used a quantitative design with an experimental approach. The study was conducted using two groups, namely the experimental group that used the Khan Academy Kids application and the control group that followed conventional learning. The subjects of this study were 60 3rd grade elementary school students at SDN Sunter Jaya 07 Jakarta. They were divided into two groups: one experimental group that used Khan Academy Kids and one control group. There was a significant increase in students' social skills in the experimental class that participated in learning using the Khan Academy Kids application, compared to students in the control class that followed conventional learning. This increase was seen from the results of the average pre-test and post-test scores, Experimental Class: from 58.2 to 78.6 while Control Class: from 56.5 to 70.3. Aspects of social skills that experienced improvement included communication, cooperation, empathy and self-control.